EFFECTIVE ORGANIZATION OF AGRICULTURAL PRODUCTION IS THE KEY TO SOLVING THE PROBLEM OF FOOD SECURITY OF THE POPULATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article discusses some aspects of ensuring food security of the population: the problem, tasks and their solution. A review of the situation in the world, regarding food security and measures to eliminate shortcomings in the field of inter-sectoral relations between countries and mechanisms for reducing the negative impact of sharp fluctuations in world market conditions on the supply of food products to the domestic market were carried A proposal is given for further improvement of legal norms aimed at ensuring the rational use of land and water resources in agriculture, achieving a higher share of food products in agricultural products.